Unveiling Radical Mediation: Navigating Body-Mind, Affect, and Technology in Media Literacy (Global Journal of Human-Social Science, 2023)
Combating disinformation fake news and hate speech has become one of the main challenges for media literacy studies Recent research reveals that affective emotional factors and confirmation bias prevail in how users interact with media content This paper draws on the conceptions of the affective turn Clough 2010 the embodied mind Varela 1990 and the concept of radical mediation Grusin 2015 to demonstrate how the body and affect act in interaction with the media producing a kind of intensification of affective interpersonal relationships generating states of mind that circulate and influence people s reactions to facts and opinions It highlights how nonconscious aspects affect conscious thinking It is concluded that strategies based on rhetorical and sociolinguistic structures are insufficient to combat disinformation It is necessary to carry out inter and transdisciplinary research that adds bodily and affective factors to the ways in which users engage with the media
Keywords: media literacy; afecctive turn; embodied cognition; radical mediation